Tania El Khoury's Live Art Collaborative Knowledge Production - McLaughlin, Laurel V.; Robbins, Carrie (Amherst College Press, 2023)
Tania El Khoury's Live Art is the first book to examine the work of Tania El Khoury, a "live" artist deeply engaged in the politics and histories of the South West Asia and North Africa (SWANA) region. Since the 2011 Syrian uprisings, El Khoury has conceived and created works about lived experiences at and across international borders in collaboration with migrants, refugees, and displaced persons as well as other artists, performers, and revolutionaries. All of El Khoury's works cross borders: between forms of artistic practice, between artists and audiences, and between art and activism. Facilitating critical dialogue about the politics of SWANA and the impact of globalization, her performances and installations also test the boundaries of aesthetic, political, and everyday norms. This interdisciplinary and multimedia reader features essays by artists, curators, and scholars who explore the dynamic possibilities and complexities of El Khoury's art. From social workers to archeologists to archivists, contributing authors engage with the radical epistemological and political revolutions that El Khoury and her collaborators invite us all to join.